(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This paper draws from a lifelong and life-wide learning and practice perspective and research to demonstrate that making visible and opening the recognition of ALL learning (formal, non-formal and informal) is a valued component of learning credentials portfolios that people bring to their lives and livelihoods. It critically examines the provocative and vexing question: Whose and what learning and recognition of learning matters? In responding to these questions, the paper illustrates some of the challenges faced by marginalized communities in making their learning visible and attaining recognition from formal institutions of learning. It presents a case for the use of more creative and learner-centred assessment and recognition approaches to make visible ALL avenues of learning, and for the expression of individual agency in seeking recognition.